PTENα Modulates CaMKII Signaling and Controls Contextual Fear Memory and Spatial Learning - Pan Wang; Fan Mei; Jiapan Hu; Minglu Zhu; Hailong Qi; Xi Chen; Ruiqi Li; Michael A. McNutt; Yuxin Yin (Cell Reports, 2017)
Summary: PTEN (phosphatase and tensin homology deleted on chromosome 10) has multiple functions, and recent studies have shown that the PTEN family has isoforms. The roles of these PTEN family members in biologic activities warrant specific evaluation. Here, we show that PTENα maintains CaMKII in a state that is competent to induce long-term potentiation (LTP) with resultant regulation of contextual fear memory and spatial learning. PTENα binds to CaMKII with its distinctive N terminus and resets CaMKII to an activatable state by dephosphorylating it at sites T305/306. Loss of PTENα impedes the interaction of CaMKII and NR2B, leading to defects in hippocampal LTP, fear-conditioned memory, and spatial learning. Restoration of PTENα in the hippocampus of PTENα-deficient mice rescues learning deficits through regulation of CaMKII. CaMKII mutations in dementia patients inhibit CaMKII activity and result in disruption of PTENα-CaMKII-NR2B signaling. We propose that CaMKII is a target of PTENα phosphatase and that PTENα is an essential element in the molecular regulation of neural activity. : Wang et al. define a specific function of PTENα in learning and memory. PTENα maintains CaMKII in an activatable state that is competent to induce long-term potentiation through dephosphorylation of CaMKII at T305/306. Long-term potentiation, contextual fear memory, and spatial learning are impaired in PTENα-specific-deficient mice. Keywords: PTENα, CaMKII, contextual fear memory, spatial learning